Functional Diversity of Diterpene Synthases in the Biofuel Crop Switchgrass. Issue 1 (15th July 2018) - Pelot, Kyle A.; Chen, Ruibing; Hagelthorn, David M.; Young, Cari A.; Addison, J. Bennett; Muchlinski, Andrew; Tholl, Dorothea; Zerbe, Philipp
Abstract : Diterpene synthases are characterized that may contribute to abiotic stress responses in the bioenergy crop switchgrass (Panicum virgatum). Abstract: Diterpenoids constitute a diverse class of metabolites with critical functions in plant development, defense, and ecological adaptation. Major monocot crops, such as maize ( Zea mays ) and rice ( Oryza sativa ), deploy diverse blends of specialized diterpenoids as core components of biotic and abiotic stress resilience. Here, we describe the genome-wide identification and functional characterization of stress-related diterpene synthases (diTPSs) in the dedicated bioenergy crop switchgrass ( Panicum virgatum ). Mining of the allotetraploid switchgrass genome identified an expansive diTPS family of 31 members, and biochemical analysis of 11 diTPSs revealed a modular metabolic network producing a diverse array of diterpenoid metabolites. In addition to ent -copalyl diphosphate (CPP) and ent -kaurene synthases predictably involved in gibberellin biosynthesis, we identified syn -CPP and ent -labda-13-en-8-ol diphosphate (LPP) synthases as well as two diTPSs forming (+)-labda-8, 13 E -dienyl diphosphate (8, 13-CPP) and ent-neo- cis-trans-clerodienyl diphosphate (CT-CLPP) scaffolds not observed previously in plants. Structure-guided mutagenesis of the (+)-8, 13-CPP and ent-neo- CT-CLPP synthases revealed residue substitutions in the active sites that altered product outcome, representing potential neofunctionalization events that occurred during diversification of the switchgrass diTPS family. The conversion of ent -CPP, ent -LPP, syn -CPP, and ent-neo -CT-CLPP by promiscuous diTPSs further yielded distinct labdane-type diterpene olefins and alcohols. Of these metabolites, the formation of 9β-hydroxy- syn -pimar-15-ene and the expression of the corresponding genes were induced in roots and leaves in response to oxidative stress and ultraviolet irradiation, indicating their possible roles in abiotic stress adaptation. Together, these findings expand the known chemical space of diterpenoid metabolism in monocot crops toward systematically investigating and ultimately improving stress resilience traits in crop species.